Study characteristical and regional influences on postpartum depression before vs. during the COVID-19 pandemic: A systematic review and meta-analysis - Xiaoqian Zhang; Xiaoqian Zhang; Chun Wang; Xiaoli Zuo; Bert Aertgeerts; Frank Buntinx; Tang Li; Mieke Vermandere (Frontiers Media S.A., 2023)
BackgroundWhile the public is under serious pressure from the coronavirus disease 2019 (COVID-19), the final impact and possible contributing factors to postpartum depression symptoms (PPDS) remain unknown. Therefore, a meta-analysis to investigate the association between PPDS and the COVID-19 pandemic was carried out by comparing the data between pre-pandemic and post-pandemic timeframes and exploring the influencing factors.MethodsThis systematic review was prospectively registered and recorded in a study protocol (Prospero CRD42022336820, http://www.crd.york.ac.uk/PROSPERO). A comprehensive search of PubMed, Embase, Web of Science, CINALH, Cochrane and Scopus was cmpleted on June 6, 2022. Studies that compared the prevalence of PPD before and during the COVID-19 pandemic period were included.ResultsOf 1766 citations identified, 22 studies were included with 15,098 participates before the COVID-19 pandemic and 11,836 participants during the COVID-19 pandemic. Overall, the analysis showed that the epidemic crisis was associated with an increased prevalence of PPDS (OR: 0.81 [0.68, 0.95], P = 0.009, I2 = 59%). Subgroup analysis was conducted according to the study characteristics and regions. Within the study characteristics classification, results showed an obvious increase in the prevalence of PPDS during the COVID-19 pandemic if PPDS cutoff was defined as Edinburgh postpartum depression score (EPDS) ≥13 points (OR: 0.72 [0.52, 0.98], P = 0.03, I2 = 67%) and an increased prevalence in follow-ups that happened after 2 weeks (≥ 2 weeks postpartum) (OR: 0.81 [0.68, 0.97], P = 0.02, I2 = 43%). Selected studies that were high-quality (OR: 0.79 [0.64, 0.97], P = 0.02, I2 = 56%) demonstrated an increased prevalence of PPDS during the COVID-19 pandemic period. Sorting by regional factors, studies conducted in Asia (OR: 0.81 [0.70, 0.93], P = 0.003, I2 = 0%) showed an increase of PPDS prevalence rates during the COVID-19 period, while studies conducted in Europe (OR: 0.82 [0.59, 1.13], P = 0.23, I2 = 71%) and North America (OR: 0.66 [0.42, 1.02], P = 0.06, I2 = 65%) showed no significant difference. All studies conducted in the developed (OR: 0.79 [0.64, 0.98], P = 0.03, I2 = 65%) and developing countries (OR: 0.81 [0.69, 0.94], P = 0.007, I2 = 0%) showed an increase of PPDS during the COVID-19 period.ConclusionsThe COVID-19 pandemic is associated with an increased prevalence of PPDS, especially after long-term follow-up and among the group with a high possibility of depression. The negative influence from the pandemic, causing more PPDS was significant in studies from Asia.